Research of safety management indicators - Dvořák, Zdeněk; Nikola Chovančíková, (Technium Social Sciences Journal, 2020)
Safety is one of the basic needs of every citizen, company, city, region, and state. Long-term solutions to safety issues have brought 6 pillars to this area (ie physical security, fire safety, safety and health at work, environmental safety and security, operational safety and security, information security). The mentioned safety/security pillars comprehensively cover the area of safety within the company, region, etc. In today's society, it is necessary to focus on the effective evaluation of individual pillars of safety/security. By evaluating them, it is possible to identify places with deficiencies that may be sources of risk in the future. Sources of risk could be identified through a tool that could comprehensively assess all pillars. The result of the evaluation would be the level of safety of the evaluated pillar. Depending on the level of the safety pillar, adequate measures could be taken to address the shortcomings.